NILAI RELIGIUS TARI SEBLANG DALAM PERSPEKTIF PAI - Imam Mashuri; Aprilia Dwi Ana Tasya (International Conference on Humanity Education and Society (ICHES), 2026)
The Seblang dance is not only an art performance but also a traditional custom with functions related to religious and community life. The Seblang Olehsari dance is performed at the beginning of the month of Syawal, which is after the Eid al-Fitr holiday. This traditional custom is performed in the form of a dance accompanied by gamelan music and a choir, with gendhing-gendhing playing in the background. The purpose of this research is to examine the religious values contained in the Seblang Olehsari Dance and analyze their relevance to Islamic Moral Education. This research uses a descriptive qualitative approach. Research subjects: Seblang Dance Committee, Religious Leaders, Moral and Ethics Teachers The data collection procedure used semi-structured interviews, non-participant observation, and documentation. Data analysis using the Miles and Huberman theory: data collection, data reduction, data presentation, and conclusions. The validity of the data is established using source triangulation. The research findings indicate that within the Seblang dance, there are religious values of Habblum minallah (relationship with God), Habblum minannas (relationship with people), and Habblum mynal alam (relationship with the universe), and all of these are relevant to the creed and morals material in Islamic Religious Education for grades X, XI, and XII.